Blood Oranges : Colonialism and Agriculture in the South Texas Borderlands - Bowman, Timothy Paul, 1978- (Book collections on Project MUSE., 2016)
Blood Oranges traces the origins and legacy of racial differences between Anglo Americans and ethnic Mexicans (Mexican nationals and Mexican Americans) in the South Texas borderlands in the twentieth century. Author Tim Bowman uncovers a complex web of historical circumstances that caused ethnic Mexicans in the region to rank among the poorest, least educated, and unhealthiest demographic in the country. The key to this development, Bowman finds, was a "modern colonization movement," a process that had its roots in the Mexican-American war of the nineteenth century but reached its culmination